Clinical Efficacy of Intersphincteric Resection for Low Rectal Cancer Compared With Abdominoperineal Resection: A Single-Center Retrospective Study. Issue 4 (April 2023) - He, Zijian; Peng, Baifu; Chen, Wenbin; Zhu, JiaDun; Chen, BaoQi; Li, Guanwei; Cao, Jie; Li, Wanglin
Background: In recent years, intersphincteric resection (ISR) has been increasingly used to replace abdominoperineal resection (APR) in the surgical treatment of ultra-low rectal cancer. Aim: This study was to compare the clinical efficacy of ISR and APR. Methods: Between 2012 and 2018, 74 consecutive patients with ultra-low rectal cancer underwent ISR or APR in our medical center. A retrospective comparison of these 2 procedures was performed. Results: A total of 43 patients underwent ISR and 31 underwent APR were included in the study. No significant differences were found between 2 groups in gender, age, BMI, and ASA score. Intersphincteric resection group showed shorter operative time ( P = .02) and less blood loss ( P = .001). Hospital stays, time to soft diet, and postoperative 30-day complications were not significantly different between the 2 groups. R0 resection achieved 100% in both the groups. As for the long-term outcomes, the survival and recurrence rate were similar between 2 groups. Moreover, the LARS and Wexner score showed that the postoperative anal function after ISR were satisfactory. Conclusion: This study suggested that ISR was feasible and safe for selected patients with ultra-low rectal cancer, with clinically superior outcomes in select patients (small tumors/further from the anal verge) and similar oncological outcomes to APR, and the anal functional outcomes after ISR were acceptable.